2009
DOI: 10.1111/j.1365-2559.2009.03462.x
|View full text |Cite
|
Sign up to set email alerts
|

BOB.1, CD79a and cyclin E are the most appropriate markers to discriminate classical Hodgkin’s lymphoma from primary mediastinal large B‐cell lymphoma

Abstract: The use of at least three of the most accurate immunohistochemical markers, cyclin E, CD79a and BOB.1, may be helpful in the differential diagnosis of cHL and PMBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…BOB1 expression was found in 40% (4/10) of cases; its positivity is typical of mature B-cell lymphomas, including diffuse large B-cell lymphoma, primary mediastinal B-cell lymphoma and nodular lymphocyte predominant Hodgkin lymphoma, but absent or weak in classical Hodgkin lymphoma, although Reed-Sternberg cells may also rarely express BOB1. 25 Hoeller et al 26 proposed an algorithm to separate primary mediastinal B-cell lymphoma and classical Hodgkin lymphoma, and to avoid the use of B-cell lymphoma, unclassifiable, by employing BOB1, CD79a and cyclin E that, according to these authors, enable accurate classification of the majority of cases of one or other type. It is worthwhile to note that in that study the authors included cases with the expression of CD20 and CD30, but the absence of CD15, without reference to CD45 status or morphological features resembling classical Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BOB1 expression was found in 40% (4/10) of cases; its positivity is typical of mature B-cell lymphomas, including diffuse large B-cell lymphoma, primary mediastinal B-cell lymphoma and nodular lymphocyte predominant Hodgkin lymphoma, but absent or weak in classical Hodgkin lymphoma, although Reed-Sternberg cells may also rarely express BOB1. 25 Hoeller et al 26 proposed an algorithm to separate primary mediastinal B-cell lymphoma and classical Hodgkin lymphoma, and to avoid the use of B-cell lymphoma, unclassifiable, by employing BOB1, CD79a and cyclin E that, according to these authors, enable accurate classification of the majority of cases of one or other type. It is worthwhile to note that in that study the authors included cases with the expression of CD20 and CD30, but the absence of CD15, without reference to CD45 status or morphological features resembling classical Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…27 Among hematolymphoid neoplasms, P63 protein has been described as positive in some types of non-Hodgkin lymphomas including diffuse large B-cell lymphoma, not otherwise specified, 26,28 primary mediastinal B-cell lymphoma 26 and anaplastic large-cell lymphoma, 29 but is absent in classical Hodgkin lymphoma. P63 expression was observed in 5 of 8 of our cases (63%), which is slightly more frequent than in the series presented by Eberle et al, 23 who found 49%.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of BCL2 and BCL6 is variable and CD10 is typically negative. In comparing CHL and PMLBCL, Hoeller et al 72 suggest that expression of BOB1 favors PMLBCL and expression of cyclin E favors CHL. Although these immunohistochemical stains are not routinely evaluated, most cases of PMLBCL express MAL, CD54, CD95, and TRAF1.…”
mentioning
confidence: 99%
“…Although these immunohistochemical stains are not routinely evaluated, most cases of PMLBCL express MAL, CD54, CD95, and TRAF1. 72 …”
mentioning
confidence: 99%
“…The WHO classification now recognizes an intermediate category of which it is not clear whether it belongs to one or the other or represents actually a separate entity. A careful study on 283 HL and 51 m-DLBL using tissue microarrays by Hoeller et al [35] shows that the markers with the highest positive predictive value for cHL were CD15, cyclin E, LMP-1 (all 100%), MUM1p (93%), and CD30 (83%). High sensitivity was achieved only by CD30 (92%) and cyclin E (79%).…”
Section: Hodgkin Lymphomamentioning
confidence: 99%